National Trends in Maternal Use of Opioid Drugs among Pregnancy-Related Hospitalizations in the United States, 1998 to 2009 - Salihu, Hamisu M.; Mogos, Mulubrhan F.; Salinas-Miranda, Abraham A.; Salemi, Jason L.; Whiteman, Valerie E. (American Journal of Perinatology, 2015)
Objective The aim of this study is to describe national trends for opioid use among pregnancy-related hospitalizations from 1998 to 2009.Study Design Using the Nationwide Inpatient Sample, we identified hospital discharge records associated with the diagnoses codes for the use of opioids for all eligible pregnancy-related inpatient admissions between 1998 and 2009. Joinpoint regression modeling was used to describe changes in trend of pregnancy-related opioid use. The main outcome measure was the annual percent change for opioids use among pregnancy-related hospitalizations.Results From 1998 to 2009, opioid use was documented in 138,224 of 55,781,966 pregnancy-related inpatient hospitalizations (25 cases per 10,000 discharges). A statistically significant downward trend occurred from 1998 to 2001, whereas from 2002 to 2009 there was a statistically significant upward trend. The increasing trend in opioid use from 2002 to 2009 is notably higher for whites compared with blacks and Hispanics.Conclusions Our findings highlight the continuous need to monitor opioids use and to revise prescription guidelines, practices, and regulatory mechanisms to curtail the progression of the increasing opioids use during pregnancy. It is critical that health care providers weight the benefits of these medications along with their potential risks when discussing analgesic treatment options with pregnant women.
Keywords: pregnancy; opioids; trends; United States